Adaptive aberration correction of abdominal images using PARCA. - Krishnan S; Rigby KW; O'Donnell M; Krishnan, S; Rigby, K W; O'Donnell, M (Ultrasonic Imaging, 1997)
Clinical images of the abdomen may be degraded by aberrations due to propagation through the abdominal wall, resulting in loss of contrast and reduction in overall image quality. The Parallel Adaptive Receive Compensation Algorithm (PARCA) uses multiple receive beams to compensate for these aberrations. Previous studies have demonstrated that PARCA can restore image quality in tissue-equivalent phantoms scanned with controlled phase and amplitude fluctuations. In this study, PARCA is used to improve clinical images of the abdomen. PARCA processed images show both improved contrast of structures and improved overall image quality.